Bone mineral density in children and young adults with neurofibromatosis type 1 - Lodish, Maya B (2012)
Concern for impaired bone health in children with neurofibromatosis type 1 (NF-1) has led to increased interest in bone densitometry in this population. Our study assessed bone mineral apparent density (BMAD) and whole-body bone mineral content (BMC)/height in pediatric patients with NF-1 with a high plexiform neurofibroma burden. Sixty-nine patients with NF-1 (age range 5.2–24.8; mean 13.7±4.8 years) were studied. Hologic dual-energy X-ray absorptiometry scans (Hologic, Inc., Bedford, MA, USA) were performed on all patients. BMD was normalized to derive a reference volume by correcting for height through the use of the BMAD, as well as the BMC. BMAD of the lumbar spine (LS 2–4), femoral neck (FN), and total body BMC/height were measured and Z-scores were calculated. Impaired bone mineral density was defined as a Z-score ≤−2. Forty-seven percent of patients exhibited impaired bone mineral density at any bone site, with 36% at the LS, 18% at the FN, and 20% total BMC/height. BMAD Z-scores of the LS (−1.60±1.26) were more impaired compared with both the FN (−0.54±1.58; P=0.0003) and the whole-body BMC/height Z-scores (−1.16±0.90; P=0.036). Plexiform neurofibroma burden was negatively correlated with LS BMAD (r(s)=−0.36, P=0.01). In pediatric and young adult patients with NF-1, LS BMAD was more severely affected than the FN BMAD or whole-body BMC/height.